Review of Gold Trading Practices on Credit (non-Cash) Based on Hadith - Sapsuha, Mubasysyyratul Ummah; Alwi, Zulfahmi; Sakka, Abdul Rahman; Al-Ayyubi, Muh. Salahuddin (LP2M IAIN Palopo, 2024)
Buying and selling gold on credit has become an increasingly popular trend in the Islamic finance industry in various countries, including Indonesia. This practice has caused debate among scholars and practitioners of Islamic finance due to its complexity involving multi-contracts and potential conflict with traditional Sharia principles regarding gold transactions. On the one hand, buying and selling gold on credit is seen as an innovation that allows wider access for the public to invest in gold. On the other hand, there are concerns that this practice could lead to riba or gharar (uncertainty) which is prohibited in Islam. This study aims to: (1) detect contracts in the sale and purchase of gold on credit, including aspects of the ability to practice hybrid contracts, and (2) examine opinions on buying and selling gold on credit, including tracing the hadiths that are used as the basis for buying and selling gold in installments or on credit. The method used in this study is a literature study with data obtained from books, journal articles, DSN-MUI fatwas, and the web sunnah.com. The results of the study show that: (1) The practice of hybrid contract in buying and selling gold on credit is allowed as long as it is in accordance with Sharia principles, by using murabahah, qard, and ijarah contracts. (2) Buying and selling gold in installments or credit may be carried out if gold is not an official medium of exchange and has shifted its function to jewelry and investment instruments.